The Impact of Adopting Relationship Marketing in Building Customer Loyalty in Banking Institutions: Study a Sample of Clients of Private Banks in the State of Jijel- - Zabat, Sami; Boukriaa, Rafika (Finance and Business Economies Review, 2022)
This study aims to test the impact of the adoption of relationship marketing on building customer loyalty in private banking institutions in the state of Jijel, as the impact of the elements of relationship marketing has been tested in empathy, commitment, communication, trust, and customer satisfaction. The sample of the study consisted of 95 clients of these institutions. The questionnaire was used as a data collection tool that included 26 items. Results were analyzed using the SPSS 23 statistical program. The results of the study indicated that there is a positive impact of the adoption of relationship marketing on customer loyalty, and this effect is due to the effect of both the element of sympathy and contentment, while the commitment, communication and trust component does not affect customer loyalty